Aromatase inhibitors for short stature in male children and adolescents treated with growth hormone: a meta-analysis of randomized controlled trials - Kan Wang; Fei Ye; Da-Yan Wang; Pan-Jian Lai; Lin-Qian Zhang (BMC Pediatrics)
Abstract Whether the addition of aromatase inhibitors (AIs) to recombinant human growth hormone (rhGH) could yield additional benefit for short stature is controversial. We aimed to assess the effects of combined AIs and rhGH versus those of rhGH alone for short stature using a meta-analytic approach. The PubMed, Embase, and the Cochrane library electronic databases were searched systematically for eligible randomized controlled trials (RCTs) from inception until December 2021. The pooled effect estimates (weighted mean difference [WMD] and odds ratio [OR]) with 95% confidence intervals (CIs) were calculated using a random-effects model. Eight RCTs that provided data on 433 participants were selected. The addition of AIs to rhGH, compared with rhGH alone, resulted in higher growth velocity (WMD: 3.19 cm/year; 95% CI: 2.75–3.63; P < 0.001), higher predicted adult height (WMD: 5.50 cm; 95% CI: 3.52–7.49; P < 0.001), and younger bone age (WMD: -0.80 years; 95% CI: -1.06–-0.54; P < 0.001). There were no significant differences between the groups for insulin-like growth factor I (WMD: 0.85 nmol/L; 95% CI: -2.08–3.79; P = 0.569), serum estradiol level (WMD: -19.19 pmol/L; 95% CI: -46.25–7.88; P = 0.165), and serum testosterone level (WMD: 14.88 nmol/L; 95% CI: -14.13–43.88; P = 0.315). There was no significant difference between the groups for the risk of adverse events (OR: 1.08; 95% CI: 0.44–2.66; P = 0.873). This study found that the addition of AIs to rhGH had greater benefits for growth velocity, predicted adult height, and bone age. The safety profiles were comparable.